Comparison Of Patchouli Oil (Pogostemon Heyneanus Benth.) Yields From Samal City; San Isidro, And Mati, Davao Oriental - Roselyn Regino (Davao Research Journal)
Patchouli oil was extracted from the air-dried leaves of Pogostemon heyneanus Benth. obtained from Brgy. Guilon, Samal City; Manikling, San Isidro, Davao Oriental and Mati, Davao Oriental by steam distillation. This study was conducted to determine a) the percentage yields of the oil, b) its physico chemicål properties, and c) whether the gathered data were within the range of international standards. Soil analyses of the sites were likewise performed to determine the amount of available nutrients in the soil and to correlate these factors with the quality of the extracted oil. The percentage yields of the oil were 0.205%, 0.197%, and 0.198% for Samal City, Sah Isidro and Mati, Davao Oriental, respectively. Except for the acid value results of the physicochemical analyses of the properties of the oil were found to be lower than the minimum requirements set by the different international standards. Results of the soil analyses revealed that patchouli plant could adapt to different soil nutrient levels and appear to have an effect on the quality of the oil.